Pendampingan Gizi di Pusat Kebugaran FAST2FIT Makassar - Ichsania, Nurul; Setyagraha, Etno; Hammado, Nurussyariah (Yayasan Daarul Huda Kruengmane, 2024)
Public awareness of the importance of fitness is increasing. In Indonesia, especially in Makassar City, people's enthusiasm can be seen from the increasing number of people exercising, both individual sports such as running and cycling, as well as people joining fitness centers. Those who do this will usually end up feeling tired or known as burn out, and in the end this will make the program fail to be implemented. In this PKM activity, it was carried out at one of the FAST2FIT fitness centers in Makassar City. The type of assistance provided starts from measuring nutritional status to education regarding managing diet according to the fitness program needs of each partner member. Apart from that, more special and intense assistance is also offered for partners who want continuous assistance. The results and activities were that 32 mentoring participants were involved in the activities, and all of them showed positive responses both when educational activities were carried out and when feedback was provided. The service activities carried out consist of tests and measurements, education, and evaluation of mentoring activities.